2022
DOI: 10.3390/nutraceuticals2040024
|View full text |Cite
|
Sign up to set email alerts
|

Ormona® SI and Ormona® RC—New Nutraceuticals with Geranylgeraniol, Tocotrienols, Anthocyanins, and Isoflavones—Decrease High-Fat Diet-Induced Dyslipidemia in Wistar Rats

Abstract: Dyslipidemia is a metabolic condition linked to increased morbidity. This study aimed to evaluate the effect of two new nutraceuticals derived from annatto (Bixa orellana), açaí (Euterpe oleracea), and soybean germ or red clover isoflavones (Trifolium pratense) against high-fat-induced dyslipidemia in female Wistar rats. The formulations were assessed through GC-MS and HPLC-UV/Vis. Next, female Wistar rats received daily administrations of coconut oil and were treated with Ormona® SI (OSI), Ormona® RC (ORC), s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…In addition, no deaths occurred in the group treated with Ormona ® at a 500 mg/kg dose. This study's histopathological analysis of the liver demonstrated that Ormona ® did not induce significant toxicity at 500 mg/kg [11].…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…In addition, no deaths occurred in the group treated with Ormona ® at a 500 mg/kg dose. This study's histopathological analysis of the liver demonstrated that Ormona ® did not induce significant toxicity at 500 mg/kg [11].…”
Section: Discussionmentioning
confidence: 67%
“…Among the isoflavones found in the T. pratense species, four bind competitively to ERα and ERβ receptors (genistein > daidzein > biochanin A > formononetin) with affinities approximately one-thousandth of 17β-estradiol [41,42]. In the phytonutraceutical Ormona ® , 5.4% daidzein, 2.3% glycitein, and 3.6% genistein were identified [11], justifying the potent estrogenic activity performed by Ormona ® .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In addition, it contains 20.8% red clover extract (Trifolium pratense), standardized with isoflavones such as daidzein, genistein, Biochanin A, and formononetin. 10% of the formulation is composed of a standardized extract of açaí (Euterpe oleracea) standardized with anthocyanins (mainly cyanidin 3-O-glucoside) (10).…”
Section: Discussionmentioning
confidence: 99%